Analisis Tingkat Kemampuan Menggiring Bola Pada Permainan Sepakbola Siswa SMA Negeri 5 Pinrang - Saharullah Saharullah; Muhammadong Muhammadong; Andi Atssam Mappanyukki; Andi Pirmansyah; Andi Supriman (Journal on Education, 2023)
The formulation of the problem in this study is how the level of dribbling ability in the soccer game of SMA Negeri 5 Pinrang students. The type of research that will be used in this research is quantitative descriptive analysis. In this research design, the research subjects were selected by total sampling with a sample of 30 people. While the data analysis used descriptive test, and frequency analysis. Based on the results of the survey of the ability to dribble in soccer games for SMA Negeri 5 Pinrang students, the results of descriptive analysis of the dribbling ability test obtained a minimum score of = 12.80 maximum score = 18. SUM = 16.566 which is the total number of test results obtained by all sample, the mean = 0.552 which is the average value of the overall test results obtained, range = 5.34 which is the middle value of the minimum and maximum values. The results of the analysis of the test frequency obtained good results 10% of 3 respondents and in the Medium category 90% of 27 respondents. So the level of dribbling ability of soccer players of SMA Negeri 5 Pinrang students is in the medium category.